Cobalt Nanoparticles Anchored on N‐Doped Porous Carbon Derived from Yeast for Enhanced Electrocatalytic Oxygen Reduction Reaction. Issue 7 (3rd February 2023) - Sun, Jiankang; Wang, Zhengyun; Xu, You; Zhang, Tiansui; Zhu, Deyu; Li, Guangfang; Liu, Hongfang
Abstract: Biomass‐derived carbon materials have received extensive attention for use in high‐performance electrocatalysts. In this study, a highly efficient electrocatalyst is developed with Co nanoparticles anchored on N‐doped porous carbon material (CoNC) by using yeast as a biomass precursor through a facial activation and pyrolysis process. CoNC exhibits comparable catalytic activity with commercial 20 % Pt/C for the oxygen reduction reaction (ORR) with a half‐wave potential of 0.854 V. A home‐made primary Zn–air battery exhibited an open circuit potential of 1.45 V and a peak power density of 188 mW cm −2 . Moreover, the discharge voltage of the primary battery maintained at a stable value up to 9 days. The enhanced performance of CoNC was probably ascribed to its high content of pyridinic‐N and graphitic‐N species, extra Co loading and porous structure, which provided sufficient active sites and channels to promote mass/electron transfer for ORR. This work provides a promising strategy to develop an efficient non‐noble metal carbon‐based electrocatalyst for fuel cells and metal–air batteries. Abstract : Beauty and the yeast : N‐doped porous carbon electrocatalyst is synthesized by the activation and pyrolysis of yeast. Additional Co‐based active sites are introduced into the porous structure by exploiting the strong interaction between activated yeast and Co–Phen complex. The obtained composite CoNC electrocatalyst demonstrates significantly enhanced catalytic activity and stability for the oxygen reduction reaction.